Cytoplasmic localization of connexin 26 suppresses transition of β‐catenin into the nucleus in intestinal‐ and mix‐type gastric cancer. Issue 4 (20th February 2022) - Nakazawa, Nobuhiro; Sohda, Makoto; Yokobori, Takehiko; Gombodorj, Navchaa; Sano, Akihiko; Sakai, Makoto; Oyama, Tetsunari; Kuwano, Hiroyuki; Shirabe, Ken; Saeki, Hiroshi
Abstract: Background: Connexin is a basic molecule that forms gap junctions and undergoes localization changes to the cytoplasm in association with carcinogenesis. We aimed to investigate and clarify the significance of cytoplasmic Cx26 expression in gastric cancer. Methods: We included 87 patients with intestinal‐ and mix‐type gastric cancer and 111 patients with diffuse type gastric cancer who underwent surgery for gastric cancer between 1999 and 2006. Immunohistochemical staining for Cx26, β‐catenin, and Wnt3a was performed and analyses of the relationship to clinicopathological factors were conducted based on the Lauren classification. In an in vitro study, the gastric cancer cell lines MKN7, MKN74, and MKN45 were used to evaluate the proliferative capacity using the water‐soluble tetrazolium salt assay through forced expression of Cx26, and the relationship between Cx26 and β‐catenin was investigated using proximity ligation assay (PLA) and co‐immunoprecipitation. Additionally, functional analysis was performed by Cage analysis. Results: In this study, high cytoplasmic Cx26 expression was associated with favorable prognosis in intestinal‐ and mix‐type gastric cancer and could be an independent prognostic factor for overall survival. In terms of the mechanism, in in vitro experiments changes in Cx26 localization to the cytoplasm were shown to suppress the change of localization of β‐catenin to the nucleus by binding to it in the cytoplasm. Conclusions: Cytoplasmic Cx26 was found to be a prognostic factor in intestinal‐ and mix‐type gastric cancer. Regarding the mechanism, in vitro studies revealed that cytoplasmic Cx26 inhibits the translocation of β‐catenin to the nucleus. Abstract : Cytoplasmic Cx26 was found to be a prognostic factor in intestinal‐ and mix‐type gastric cancer. We revealed that cytoplasmic Cx26 inhibits the translocation of β‐catenin to the nucleus.